Bullshit jobs [compact disc, unabridged] - Graeber, David (Simon & Schuster Audio, 2018)
A powerful argument against the rise of meaningless, unfulfilling jobs, and their consequences. Gives individuals, corporations, and societies permission to undergo a shift in values, placing creative and caring work at the center of our culture. This book is for everyone who wants to turn their vocation back into an avocation.